The advantages of using augmented reality as a pedagogical teaching resource - Soriano-Sánchez, José-Gabriel (2023)
Augmented reality (AR) has been described as an interactive platform that presents a combination of virtual and real-world elements. Educators must incorporate ICT in the classroom and understand that its primary advantage is to enhance and facilitate the teaching-learning process of the learner. The aim of this paper is to identify, through a systematic review, the advantages of AR as a pedagogical teaching tool. To this end, a search for articles was carried out in different databases, such as Web of Science and Scopus. A total of 529 studies were obtained and, after applying the established inclusion criteria, 38 papers were left for review. The results showed that when AR-based activities are integrated, students of any educational level suggest a higher motivation and academic performance, considering this innovative resource as a more fun and interactive way of learning. In conclusion, it would be interesting to implement AR as a standard approach to learning, given its innovative character and the multiple benefits derived from its interactive nature, immediacy and student motivation.